Japanese American midwives culture, community, and health politics, 1880 - 1950 - Smith, Susan Lynn (The Asian American experience, 2005)
In the late 19th century, midwifery was transformed into a new women's profession by modernizing Japan. As emigration to the U.S. increased, so Japanese midwives became involved as cultural brokers & participated in the creation of a Japanese American identity.